Tkinter GUI Application Development Cookbook : a practical solution to your GUI development problems with Python and Tkinter. - Rodas de Paz, Alejandro (Packt Publishing, 2018)
As one of the more versatile programming languages, Python is well-known for its batteries-included philosophy, which includes a rich set of modules in its standard library; Tkinter is the library included for building desktop applications. Due to this, Tkinter is a common choice for rapid GUI development, and more complex applications can ...